Cardioprotective Effect of Echinatin Against Ischemia/Reperfusion Injury: Involvement of Hippo/Yes-Associated Protein Signaling - Niu, Jieting; Li, Yanguang; Song, Xiang; Liu, Yunfeng; Li, Ying; Li, Ya (Frontiers in Pharmacology, 2021)
Background: Echinatin (Ech) has been reported to exert antioxidant and anti-inflammatory activities. In this study, we aimed to characterize the functional role of Ech in myocardial ischemic/reperfusion (MI/R) injury and elucidate its underlying mechanism of action. Method: We established in vivo and in vitro models of MI/R injury to determine the effect of Ech on MI/R injury. Gene expression was examined using quantitative real-time polymerase chain reaction and western blotting. Myocardial infarction was assessed using tetrazolium chloride staining and the degree of myocardial injury was evaluated by measuring lactate dehydrogenase (LDH) and creatine kinase-myocardial band (CK-MB) levels. Cell apoptosis was detected using the terminal deoxynucleotidyl transfer-mediated dUTP nick end-labeling (TUNEL) assay. The viability of H9c2 cells was determined using Cell Counting Kit-8 assay. Results: MI/R induced myocardial infarction, which was mitigated by Ech treatment. Moreover, Ech treatment resulted in a marked decline of LDH and CK-MB levels in the serum and myocardium of MI/R rats. Ech treatment also restrained cardiomyocyte apoptosis in vivo and in vitro, as evidenced by reduction in LDH release, the number of TUNEL-positive cells, and caspase-3 activity. Furthermore, Ech administration inhibited MI/R-induced activation of Hippo/Yes-associated protein signaling in vivo and in vitro, as indicated by inhibition of mammalian sterile 20-like protein kinase 1, large tumor suppressor 1, and YAP phosphorylation and promotion of YAP nuclear translocation. However, silencing of YAP counteracted the protective effect of Ech on hypoxia/reoxygenation-induced myocardial injury in vitro. Conclusion: Ech exerted its protective effect against MI/R injury at least partially by suppressing the Hippo/YAP signaling pathway, providing novel insights into the remission of MI/R injury.